Adverse Pregnancy Outcomes among Women Who Conceive on Antiretroviral Therapy - Risa M. Hoffman (2019)
© The Author(s) 2018. Published by Oxford University Press for the Infectious Diseases Society of America. All rights reserved. Background. Adverse pregnancy outcomes for women who conceive on antiretroviral therapy (ART) may be increased, but data are conflicting. Methods. Human immunodeficiency virus-infected, nonbreastfeeding women with pre-ART CD4 counts ?400 cells/?L who started ART during pregnancy were randomized after delivery to continue ART (CTART) or discontinue ART (DCART). Women randomized to DCART were recommended to restart if a subsequent pregnancy occurred or for clinical indications. Using both intentto- treat and as-treated approaches, we performed Fisher exact tests to compare subsequent pregnancy outcomes by randomized arm. Results. Subsequent pregnancies occurred in 277 of 1652 (17%) women (CTART: 144/827; DCART: 133/825). A pregnancy outcome was recorded for 266 (96%) women with a median age of 27 years (interquartile range [IQR], 24-31 years) and median CD4+ T-cell count 638 cells/?L (IQR, 492-833 cells/?L). When spontaneous abortions and stillbirths were combined, there was a significant difference in events, with 33 of 140 (23.6%) in the CTART arm and 15 of 126 (11.9%) in the DCART arm (relative risk [RR], 2.0 [95% confidence interval CI, 1.1-3.5]; P = .02). In the as-treated analysis, the RR was reduced and no longer statistically significant (RR, 1.4 [95% CI, .8-2.4]). Conclusions. Women randomized to continue ART who subsequently conceived were more likely to have spontaneous abortion or stillbirth, compared with women randomized to stop ART; however, the findings did not remain significant in the as-treated analysis. More data are needed on pregnancy outcomes among women conceiving on ART, particularly with newer regimens.